Note on Order-Isomorphic Isometric Embeddings of Some Recent Function Spaces. (8th June 2015) - Talponen, Jarno
Abstract : We investigate certain recently introduced ODE-determined varying exponentL p spaces. It turns out that these spaces are finitely representable in a concrete universal varying exponentl p space. Moreover, this can be accomplished in a natural unified fashion. This leads to order-isomorphic isometric embeddings of all of the aboveL p spaces to an ultrapower of the above varying exponentl p space.